"Sødssund" – ett försvunnet jämtländskt bebyggelsenamn - Holm, Olof (NAMN OG NEMNE, 2023)
Sødssund – a lost Jämtland settlement name A settlement name in the parish of Revsund in Jämtland (in present-day Sweden) is recorded in a letter from 1451 as Søødzsund. The author locates the name to the village of Sund and interprets it as ‘Sauðs or Søds farm in Sund’. In Jämtland, there are several examples of similar names from the late Middle Ages, comprising a personal name and the name of the village. The first element should be seen as referring to the name of a previous owner or tenant. In this case, this would most likely have been a man recorded as Nils Sowdher/Sodher in 1410 and 1412. The man’s byname (Old Norse Sauðr, Old Swedish Sødh) meant ‘sheep’.